The Beautiful, Novel, and Strange : Aesthetics and Heterodoxy - Paulson, Ronald (Book collections on Project MUSE., 2019)
In The Beautiful, Novel, and Strange Ronald Paulson fills a lacuna in studies of aesthetics at its point of origin in England in the 1700s. He shows how aesthetics took off not only from British empiricism but also from such forms of religious heterodoxy as deism. The third earl of Shaftesbury, the founder of aesthetics, replaced the Christian God of rewards and punishments with beauty - worship of God, with a taste for a work of art. William Hogarth, reacting against Shaftesbury's "disinterestedness," replaced his Platonic abstractions with an aesthetics centered on the human body, gendered female, and based on an epistemology of curiosity, pursuit, and seduction. Paulson shows Hogarth creating, first in practice and then in theory, a middle area between the Beautiful and the Sublime by adapting Joseph Addison's category (in the Spectator) of the Novel, Uncommon, and Strange